Aluminum and aluminum alloy based non-oxide ceramic composite material, preparation method and application

By using low-melting point resin and paraffin as binders in aluminum-based composite materials, combined with photocuring, cooling curing and binder jetting technology, and combined with cold isostatic pressing and hot pressing sintering processes, the problems of molding accuracy and processing performance of traditional aluminum-based composite ceramic materials are solved, and the preparation of high-precision and low-cost aluminum-based non-oxide ceramic composite materials are achieved.

CN119753401APending Publication Date: 2025-04-04NAT INST CORP OF ADDITIVE MFG XIAN
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411664094.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The molding method of traditional aluminum-based composite ceramic materials cannot achieve high-precision molding of complex structures, and the addition of super-hard non-oxide ceramic particles reinforced phases makes the material's cutting and processing performance very poor, limiting its practical application.

Method used

Low melting point resin and paraffin are used as binders, and alternately combined by photocuring and cooling curing, combined with binder jet technology to deposit and cure layer by layer, forming a mixed powder blank with aluminum-based metal and non-oxide ceramics, and through cold isostatic pressing and hot pressing sintering densification process.

Benefits of technology

High-precision integrated clean forming is achieved, solving the problems of composite molding and difficult processing of metal and ceramics, improving the high-temperature mechanical properties, thermal characteristics and tribological properties of the material, simplifying the preparation process, and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753401A_ABST
    Figure CN119753401A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of aluminum-based composite materials, and discloses an aluminum and aluminum alloy-based non-oxide ceramic composite material, a preparation method and an application. Non-oxide ceramic powder and aluminum and aluminum alloy powder are proportioned and ball-milled to obtain a prepared mixed powder; acrylic resin monomer and paraffin are proportioned and stirred, and a photoinitiator is added during the stirring process to obtain a binder; a binder injection technology is used to obtain a metal ceramic composite green body with a certain complex shape, and finally a non-oxide ceramic reinforced aluminum and aluminum alloy-based composite material is obtained through post-curing, isostatic pressing, degreasing, sintering and other processes. The present invention innovatively combines temperature reduction curing and light curing for alternating curing. By using low-melting point acrylic resin monomers and paraffin as binders, not only the plasticity and processability of the material are improved, but also the curing process is made more flexible, effectively improving the high-temperature mechanical properties, thermal properties and tribological properties of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of aluminum-based composite materials, and in particular to an aluminum and aluminum alloy-based non-oxide ceramic composite material, a preparation method and application thereof. Background Art

[0002] In response to low-carbon green development, the aerospace and automotive fields are facing pressure to manufacture lighter and more efficient power locomotives. Lightweight aluminum alloys are used to make the locomotive lighter overall. Composite materials have been proven to reduce aircraft weight by 15% to 40%, thereby reducing fuel consumption. Aluminum and aluminum alloys are widely used as matrix materials for metal and ceramic composite systems due to their low density, strong plasticity, high specific strength, specific stiffness, specific modulus and other advantages.

[0003] However, the mechanical, corrosion and wear resistance of single aluminum and aluminum alloy materials cannot meet the use requirements. As a widely used composite material, the use requirements of aluminum-based composite materials have gradually evolved from the initial pursuit of single performance to high strength and toughness and structural function integration. At the same time, non-oxide reinforced aluminum and aluminum alloy-based composite ceramic materials have high specific strength and specific stiffness, low thermal expansion coefficient, low density, high micro-yield strength, good dimensional stability, thermal conductivity, as well as excellent mechanical and physical properties such as wear resistance and fatigue resistance, and are widely used in aerospace, military, automotive, electronics, sports equipment and other fields.

[0004] Traditional aluminum-based composite ceramic material forming methods, including molding, casting and powder metallurgy, all require secondary machining to achieve the required precision and surface roughness requirements of parts. The addition of ultra-hard non-oxide ceramic particle reinforcement phase makes the material's cutting performance very poor, thus limiting its practical application. In addition, this forming method cannot achieve high-precision forming of complex structures.

[0005] Although the Chinese patent publication number is CN108034866A, and the name is a high-performance silicon nitride aluminum-based composite material and its preparation method, a molding method is adopted, silicon nitride powder and aluminum-based powder are ball-milled and mixed, and then spark plasma (SPS) sintering densification is performed, but the conventional molding of this method cannot meet the molding requirements of complex structural parts, and spark plasma sintering has potential radiation. Summary of the invention

[0006] In view of the problems mentioned in the prior art, the present invention proposes an aluminum and aluminum alloy-based non-oxide ceramic composite material, a preparation method and an application thereof, wherein a low-melting-point resin and paraffin are selected as binders, and light curing and temperature reduction curing are alternately combined. The binder is sprayed to deposit and solidify layer by layer to form an aluminum-based metal and non-oxide ceramic mixed powder blank, and then a cold isostatic pressing and press sintering densification process is used to optimize the problem of large voids in the spray deposition molding material, and finally an aluminum and aluminum alloy-based non-oxide ceramic composite material is formed, achieving high-precision integrated net molding, and solving the problems of metal and ceramic composite molding and difficult processing.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: The present invention provides a method for preparing an aluminum and aluminum alloy-based non-oxide ceramic composite material, comprising the following steps: S1, mixing and ball-milling non-oxide ceramic powder and aluminum and aluminum alloy powder to obtain a prepared mixed powder; S2, taking acrylic resin monomer and paraffin, mixing and stirring, adding a photoinitiator during the stirring process, to obtain a binder; S3, using a binder jetting technique to obtain a metal-ceramic composite body by mixing the mixed powder obtained in step S1 with the binder obtained in step S2; S4, placing the metal-ceramic composite material body into a curing box for curing, and then performing an isostatic pressing, and placing the metal-ceramic composite material body after isostatic pressing into a degreasing furnace for degreasing; S5, decarbonizing the degreased metal-ceramic composite material body, performing secondary isostatic pressing on the metal-ceramic composite material body after decarbonization, and hot-pressing and sintering the isostatically pressed metal-ceramic composite material body to obtain a metal-ceramic composite material component.

[0008] As a further improvement of the present invention, the non-oxide ceramic powder in step S1 can be one or more of silicon carbide, silicon nitride, aluminum nitride, and boron carbide; The mass of non-oxide ceramic powder is 0-40wt%, and the mass of aluminum and aluminum alloy powder is 60-100wt%.

[0009] As a further improvement of the present invention, during ball milling in step S1, the mass ratio of grinding balls to powder is 1:1-2; The ball milling time is 2 to 10 hours.

[0010] As a further improvement of the present invention, the acrylic resin monomer in step S2 may be stearic acid methacrylate monomer, or one or more resin monomers with a freezing point of less than 30°C; The mass ratio of acrylic acid monomer to paraffin is 4:1; The photoinitiator accounts for 1% to 5% of the total mass of the acrylic monomers.

[0011] As a further improvement of the present invention, the photoinitiator may be one or more of TPO, 819, and 651.

[0012] As a further improvement of the present invention, the specific process of step S4 is: Put the metal-ceramic composite body into a curing box and cure it for 1 to 4 hours at a temperature of 25 to 35°C; The cured metal-ceramic composite body is sprayed with a 1% calcium chloride solution, coated with latex, and vacuumed for 2 hours; After vacuuming, perform isostatic pressing at a pressure of 80-120 MPa and a time of 60-120 s; The isostatically pressed metal-ceramic composite body is placed in an argon furnace for degreasing.

[0013] As a further improvement of the present invention, the degreasing process is specifically: The temperature is raised at a first heating rate, and when the temperature is raised to a temperature close to the degreasing temperature, the temperature is raised at a second heating rate to the degreasing temperature and kept warm for 2 to 4 hours; The first heating rate is 2-5°C / min; The second heating rate is 0.5-2°C / min; The degreasing temperature is 300-550℃.

[0014] As a further improvement of the present invention, the specific process of step S5 is: The degreased metal-ceramic composite body is placed in a sintering furnace at room temperature, heated to 300°C at a heating rate of 0.5-1°C / min, kept at this temperature for 1-2 hours, subjected to low-temperature decarbonization, and cooled to room temperature at a cooling rate of 0.5-2°C / min; The temperature is raised again to 500°C at a heating rate of 0.5-1°C / min, kept at this temperature for 1-2 hours for high-temperature decarbonization, and then cooled to room temperature; The metal-ceramic composite body after carbon removal is sprayed with a 1% calcium chloride solution, coated with latex, and vacuumed for 2 hours, and isostatically pressed for the second time at a pressure of 80 to 160 MPa and a time of 60 to 120 seconds; The metal-ceramic composite material green body after isostatic pressing is subjected to hot pressing sintering, the sintering temperature is 400-2000° C., the heat preservation time is 2-6 hours, and the pressure is 10-200 MPa.

[0015] The invention discloses an aluminum and aluminum alloy based non-oxide ceramic composite material obtained by a preparation method of an aluminum and aluminum alloy based non-oxide ceramic composite material.

[0016] As a further improvement of the present invention, the application includes at least one of the following: Application in aerospace inertial materials; Application in satellite solar reflector materials; Application in automobile piston bearing materials; Application in electronic packaging materials.

[0017] Compared with the prior art, the present invention has achieved the following technical effects: The method of the present invention combines temperature curing and light curing alternately, and uses low-melting-point acrylic resin monomers and paraffin as binders, which not only improves the plasticity and processability of the material, but also makes the curing process more flexible, effectively improving the high-temperature mechanical properties, thermal properties and tribological properties of the material.

[0018] The metal-ceramic composite material blank prepared by the binder injection molding technology of the present invention has uniform component distribution and continuous and dense structure. Compared with the traditional preparation method, this technology not only simplifies the preparation process and reduces production costs, but also ensures the stability and consistency of product quality.

[0019] In order to solve the problem of insufficient density of binder sprayed parts, the present invention combines binder spraying with cold isostatic pressing and hot pressing sintering technology, which effectively solves this problem. Cold isostatic pressing technology uses high pressure to make the particles inside the material more densely arranged; while hot pressing sintering promotes the fusion and diffusion between material particles under high temperature and high pressure, further improving the density and strength of the material.

[0020] The present invention gets rid of the dependence of traditional processing methods on molds, realizes the batch preparation of aluminum and aluminum alloy-based non-oxide ceramic composite parts, and at the same time, can also meet the molding needs of complex parts, providing more possibilities and choices for aerospace, automobile manufacturing, and other high-end manufacturing fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the preparation method of the present invention; Figure 2 This is a physical picture of the aluminum and aluminum alloy based non-oxide ceramic composite material of the present invention. DETAILED DESCRIPTION

[0022] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0023] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0024] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0025] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or a communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0026] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0027] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0028] It should also be understood that the terms used in the present specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the present specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0029] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0030] Various structural schematic diagrams of the embodiments disclosed in the present invention are shown in the accompanying drawings. These figures are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the figures and the relative sizes and positional relationships therebetween are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may additionally design regions / layers with different shapes, sizes, and relative positions according to actual needs.

[0031] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0032] The method for preparing aluminum and aluminum alloy-based non-oxide ceramic composite materials of the present invention selects low-melting point resin monomers and paraffin wax as binders, forms a green body of metal and non-oxide ceramic mixed powder through binder jetting (BJ) technology, and then successfully prepares high-strength and high-precision aluminum and aluminum alloy-based non-oxide ceramic composite material components through secondary cold isostatic pressing and hot isostatic pressing sintering processes of the green body.

[0033] Step 1: Take non-oxide ceramic powder and aluminum and aluminum alloy powder, mix and ball-mill to obtain a prepared mixed powder. In the embodiment, the non-oxide ceramic powder can be one or more of silicon carbide, silicon nitride, aluminum nitride, and boron carbide. The non-oxide ceramic powder is used as a reinforcement. Through the binder jetting (BJ) technology, integrated net molding can be achieved without secondary processing, which solves the problem that in the secondary processing of the traditional preparation method, the material has very poor cutting performance and is difficult to process due to the addition of ultra-hard reinforcement phase particles in too high an amount, high brittleness, and low toughness. In the embodiment, the mass of the non-oxide ceramic powder is 0-40wt%, and the mass of the aluminum and aluminum alloy powder is 60-100wt%. They are added to a ball mill and ball-milled for 2-10 hours, and the mass ratio of the grinding balls to the powder is 1:1-2.

[0034] Step 2: Take acrylic resin monomer and paraffin, mix and stir, add photoinitiator during stirring, and obtain adhesive. The adhesive in the embodiment can be solid at room temperature (<30°C), and change to liquid when heated to (30-100°C), and the solid-liquid physical state transition is reversible. Through this characteristic, it can combine cooling curing and photocuring. Since stearic acid methacrylate and paraffin have the characteristics of cooling solidification and curing at the same time, in addition, stearic acid methacrylate resin monomer is photocured and polymerized and cross-linked, and the curing reaction can be carried out at a lower temperature, which can avoid thermal damage to the material. ; In the embodiment, the acrylic resin monomer is preferably stearic acid methyl acrylate monomer, but is not limited thereto, and may also be other composite low-temperature (<30°C) solidified or Tg≤38°C resin monomers can be replaced, the acrylic resin monomer and paraffin are put into a blender and stirred to dissolve after adding a photoinitiator, the photoinitiator is used for curing of photocurable materials, wherein the mass ratio of acrylic monomer to paraffin is 4:1; the initiator accounts for 1% to 5% of the total mass of the acrylic monomer, and the photoinitiator may be one or more of TPO, 819, 651.

[0035] Step 3: Load the mixed powder obtained in step S1 and the binder obtained in step S2 into a binder spraying device, and use the binder spraying technology to obtain a metal-ceramic composite body. The hot extrusion temperature of the binder is 80-150°C.

[0036] Step 4: Place the spray-deposited body into a curing box to cross-link and cure the body. The curing time is 1 to 4 hours and the temperature of the curing box is 25 to 35°C. Primary isostatic pressing: The post-cured body is first latex-coated and vacuum-treated, and then cold isostatically pressed once, with a holding time of 60 to 120 seconds and a pressure of 80 to 120 MPa.

[0037] The metal-ceramic composite body after the primary cold isostatic pressing is placed in the debinding furnace for debinding. The debinding temperature is determined according to the thermogravimetric curve. The temperature range with the largest mass loss is selected as the debinding temperature, which is generally 300-550°C. In order to ensure that the organic binder is completely removed during the debinding process, the holding time is 2-4 hours. In order to reduce the defects such as cracks, bulges and interlayer peeling caused by the excessively fast heating rate and inappropriate insulation stage during the debinding process, which greatly affect the strength of the final sintered parts, a gradient heating mode is adopted. The heating rate is controlled at 2-5°C / min or above before reaching the debinding temperature. When approaching the debinding temperature, the heating rate is reduced to 0.5-2°C / min or below.

[0038] Step 5: Use the wave decarburization process to decarburize the degreased blank in the air to prevent cracking. Raise the temperature to 300℃ at 0.5~1℃ / min and keep it for 1~2h for low-temperature decarburization, then cool it down to room temperature at 0.5~2℃ / min; then raise the temperature to 500℃ at 0.5~1℃ / min and keep it for 1~2h for high-temperature decarburization, and then cool it to room temperature with the furnace.

[0039] The decarbonized green body is latex coated and vacuumed, and then subjected to secondary cold isostatic pressing, with a holding time of 60s to 120s and a pressure of 80MPa to 160MPa.

[0040] The green body after secondary isostatic pressing is subjected to hot pressing sintering densification, the sintering temperature is 400-2000°C, the holding time is 2h-6h, and the pressure is 10-200MPa, and finally a dense aluminum and aluminum alloy-based non-oxide ceramic composite material component is obtained.

[0041] Example 1 Step 1: Select 10 μm silicon carbide ceramic powder and aluminum alloy powder AlSiMg10, where the mass of silicon carbide ceramic powder is 12.70 g and the mass of aluminum alloy powder is 25 g, add them into a ball mill and ball mill for 2 hours to obtain a mixed powder.

[0042] Step 2: Select stearic acid methacrylate monomer and paraffin, wherein the stearic acid methacrylate monomer and paraffin are 4g and 1g respectively, dissolve the mixed adhesive at 80°C, add 0.12g TPO and stir to dissolve, to obtain an adhesive.

[0043] Step 3: Add the mixed powder and binder into the binder jetting equipment, solidify layer by layer through the 3D printing model, and make the SiC reinforced AlSiMg10 part blank at 80°C.

[0044] Step 4: Place the part blank in a curing box and cure it for 1 hour at a temperature of 25°C; then spray a 1% calcium chloride solution on the cured part, cover it with latex, and evacuate it for 2 hours. Perform a cold isostatic pressing at a pressure of 80 MPa for 60 seconds. After isostatic pressing at room temperature, place it in an argon furnace and heat it to 280°C at a rate of 2°C / min. Then, heat it to a degreasing temperature of 350°C at a rate of 1°C / min and keep it for 2 hours for degreasing.

[0045] Step 5: The degreased green body is placed in a sintering furnace at room temperature, heated to 300°C at a heating rate of 1°C / min, kept at this temperature for 1 hour, and then cooled to room temperature at a cooling rate of 1°C / min; then heated to 500°C at a heating rate of 1°C / min, kept at this temperature for 1 hour, and then cooled; The metal-ceramic composite body after carbon removal was sprayed with a 1% calcium chloride solution, covered with latex, and vacuumed for 2 hours, and subjected to secondary isostatic pressing at a pressure of 80 MPa and a time of 60 seconds; Under the conditions of sintering temperature of 1300℃ and 110MPa and keeping warm for 2h, high-density SiC reinforced AlSiMg10 parts were obtained.

[0046] Example 2 Step 1: Select 10μm silicon nitride ceramic powder and aluminum alloy powder AlSiMg10, where the mass of the silicon nitride ceramic powder is 26.98g and the mass of the aluminum alloy powder is 50g, add them into a ball mill and ball mill for 8h to obtain a mixed powder.

[0047] Step 2: Select stearic acid methacrylate monomer and paraffin, wherein the stearic acid methacrylate monomer and paraffin are 8g and 2g respectively, dissolve the mixed adhesive at 100°C, add 0.24g of photoinitiator 819 and stir to dissolve, to obtain an adhesive.

[0048] Step 3: Add the mixed powder and binder into the binder jetting equipment, solidify layer by layer through the 3D printing model, and make the Si3N4 reinforced AlSiMg10 part blank at 150°C.

[0049] Step 4: Place the part blank in a curing box and cure it for 4 hours at a temperature of 35°C; then spray a 1% calcium chloride solution on the cured part, cover it with latex, and evacuate it for 2 hours. Perform a cold isostatic pressing at a pressure of 120 MPa and maintain the pressure for 120 seconds. After isostatic pressing at room temperature, place it in an argon furnace and heat it to 500°C at a rate of 5°C / min. Then, heat it to a degreasing temperature of 550°C at a rate of 2°C / min and keep it for 4 hours for degreasing.

[0050] Step 5: The degreased green body is placed in a sintering furnace at room temperature, heated to 300°C at a heating rate of 0.5°C / min, kept at this temperature for 2 hours, and then cooled to room temperature at a cooling rate of 2°C / min; then heated to 500°C at a heating rate of 1°C / min, kept at this temperature for 2 hours, and then cooled; The metal-ceramic composite body after carbon removal was sprayed with a 1% calcium chloride solution, covered with latex, and vacuumed for 2 hours, and subjected to secondary isostatic pressing at a pressure of 160 MPa and a time of 120 seconds; Under the conditions of sintering temperature of 1200℃ and 80MPa and keeping warm for 6h, high-density Si3N4 reinforced AlSiMg10 parts were obtained.

[0051] Example 3 Step 1: Select 8μm aluminum nitride ceramic powder and aluminum alloy powder AlSiMg10, where the mass of the aluminum nitride ceramic powder is 24.21g and the mass of the aluminum alloy powder is 50g, add them into a ball mill and ball mill for 5h to obtain a mixed powder.

[0052] Step 2: Select stearic acid methacrylate monomer and paraffin, wherein the stearic acid methacrylate monomer and paraffin are 8g and 2g respectively, dissolve the mixed adhesive at 90°C, add 0.18g of photoinitiator 651 and stir to dissolve, to obtain an adhesive.

[0053] Step 3: Add the mixed powder and binder into the binder jetting equipment, solidify layer by layer through the 3D printing model, and make the AlN reinforced AlSiMg10 part blank at 120°C.

[0054] Step 4: Place the part blank in a curing box and cure it for 2.5 hours at a temperature of 30°C; then spray a 1% calcium chloride solution on the cured part, cover it with latex, and evacuate it for 2 hours. Perform a cold isostatic pressing at a pressure of 100 MPa and maintain the pressure for 90 seconds. After isostatic pressing at room temperature, place it in an argon furnace and heat it to 400°C at a rate of 3°C / min. Then, heat it to a degreasing temperature of 450°C at a rate of 1.5°C / min and keep it for 3 hours for degreasing.

[0055] Step 5: The degreased green body is placed in a sintering furnace at room temperature, heated to 300°C at a heating rate of 1°C / min, kept at this temperature for 1.5 hours, and then cooled to room temperature at a cooling rate of 2°C / min; then heated to 500°C at a heating rate of 1°C / min, kept at this temperature for 1.5 hours, and then cooled; The metal-ceramic composite body after carbon removal was sprayed with a 1% calcium chloride solution, covered with latex, and vacuumed for 2 hours, and subjected to secondary isostatic pressing at a pressure of 120 MPa and a time of 90 seconds; Under the conditions of sintering temperature of 1400℃ and 110MPa and keeping warm for 4h, high-density AlN reinforced AlSiMg10 parts were obtained.

[0056] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.

[0057] In addition, it should be understood that although this specification is described in accordance with the implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. The above content is only to illustrate the technical idea of ​​the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution according to the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing aluminum and aluminum alloy-based non-oxide ceramic composite materials, characterized in that: The following steps are involved: S1, mixing and ball-milling non-oxide ceramic powder and aluminum and aluminum alloy powder to obtain a prepared mixed powder; S2, taking acrylic resin monomer and paraffin, mixing and stirring, adding a photoinitiator during the stirring process, to obtain a binder; S3, using a binder jetting technique to obtain a metal-ceramic composite body by mixing the mixed powder obtained in step S1 with the binder obtained in step S2; S4, placing the metal-ceramic composite material body into a curing box for curing, and then performing an isostatic pressing, and placing the metal-ceramic composite material body after isostatic pressing into a degreasing furnace for degreasing; S5, decarbonizing the degreased metal-ceramic composite body, performing secondary isostatic pressing on the metal-ceramic composite body after decarbonization, and hot-pressing and sintering the isostatically pressed metal-ceramic composite body to obtain a metal-ceramic composite component.

2. The method for preparing an aluminum and aluminum alloy-based non-oxide ceramic composite material according to claim 1, characterized in that: The non-oxide ceramic powder in step S1 may be one or more of silicon carbide, silicon nitride, aluminum nitride, and boron carbide; The mass of non-oxide ceramic powder is 0-40wt%, and the mass of aluminum and aluminum alloy powder is 60-100wt%.

3. The method for preparing an aluminum and aluminum alloy-based non-oxide ceramic composite material according to claim 1, characterized in that: During ball milling in step S1, the mass ratio of grinding balls to powder is 1:1-2; The ball milling time is 2 to 10 hours.

4. The method for preparing an aluminum and aluminum alloy-based non-oxide ceramic composite material according to claim 1, characterized in that: The acrylic resin monomer in step S2 may be stearic acid methacrylate monomer, or one or more resin monomers with a freezing point of less than 30°C; The mass ratio of acrylic acid monomer to paraffin is 4:1; The photoinitiator accounts for 1% to 5% of the total mass of the acrylic monomers.

5. The method for preparing an aluminum and aluminum alloy-based non-oxide ceramic composite material according to claim 4, characterized in that: The photoinitiator can be one or more of TPO, 819, and 651.

6. The method for preparing an aluminum and aluminum alloy-based non-oxide ceramic composite material according to claim 1, characterized in that: The specific process of step S4 is: Put the metal-ceramic composite body into a curing box and cure it for 1 to 4 hours at a temperature of 25 to 35°C; The cured metal-ceramic composite body is sprayed with a 1% calcium chloride solution, coated with latex, and vacuumed for 2 hours; After vacuuming, perform isostatic pressing at a pressure of 80-120 MPa and a time of 60-120 s; The isostatically pressed metal-ceramic composite body is placed in an argon furnace for degreasing.

7. A method for preparing aluminum and aluminum alloy-based non-oxide ceramic composite materials according to claim 6, characterized in that: The degreasing process is as follows: The temperature is raised at a first heating rate, and when the temperature is raised to a temperature close to the degreasing temperature, the temperature is raised at a second heating rate to the degreasing temperature and kept warm for 2 to 4 hours; The first heating rate is 2-5°C / min; The second heating rate is 0.5-2°C / min; The degreasing temperature is 300-550℃.

8. The method for preparing an aluminum and aluminum alloy-based non-oxide ceramic composite material according to claim 1, characterized in that: The specific process of step S5 is: The degreased metal-ceramic composite body is placed in a sintering furnace at room temperature, heated to 300°C at a heating rate of 0.5-1°C / min, kept at this temperature for 1-2 hours, subjected to low-temperature decarbonization, and cooled to room temperature at a cooling rate of 0.5-2°C / min; The temperature is raised again to 500°C at a heating rate of 0.5-1°C / min, kept at this temperature for 1-2 hours for high-temperature decarbonization, and then cooled to room temperature; The metal-ceramic composite body after carbon removal is sprayed with a 1% calcium chloride solution, coated with latex, and vacuumed for 2 hours, and isostatically pressed for the second time at a pressure of 80 to 160 MPa and a time of 60 to 120 seconds; The metal-ceramic composite material green body after isostatic pressing is subjected to hot pressing sintering, the sintering temperature is 400-2000° C., the heat preservation time is 2-6 hours, and the pressure is 10-200 MPa.

9. The aluminum and aluminum alloy based non-oxide ceramic composite material obtained according to the method for preparing the aluminum and aluminum alloy based non-oxide ceramic composite material according to any one of claims 1 to 8.

10. Application of the aluminum and aluminum alloy-based non-oxide ceramic composite material according to claim 9, wherein the application comprises at least one of the following: Application in aerospace inertial materials; Application in satellite solar reflector materials; Application in automobile piston bearing materials; Application in electronic packaging materials.

Citation Information

Patent Citations

  • High-performance silicon nitride aluminum matrix composite and preparation method thereof

    CN108034866A